Different Anatomical Subsites of Colon Cancer and Mortality: A Population-Based Study - Xing-kang He; Wenrui Wu; Yu-e Ding; Yue Li; Lei-min Sun; Jianmin Si (Gastroenterology Research and Practice)
Background. In terms of incidence and pathogenesis, right-sided colon cancer (RCC) and left-sided colon cancer (LCC) exhibit several differences. However, whether existing differences could reflect the different survival outcomes remains unclear. Therefore, we aimed to ascertain the role of location in the prognosis. Methods. We identified colon cancer cases from the Surveillance, Epidemiology, and End Results database between 1973 and 2012. Differences among subsites of colon cancer regarding clinical features and metastatic patterns were compared. The Kaplan-Meier curves were conducted to compare overall and disease-specific survival in relation to cancer location. The effect of tumour location on overall and cancer-specific survival was analysed by Cox proportional hazards model. Results. A total of 377,849 patients from SEER database were included in the current study, with 180,889 (47.9%) RCC and 196,960 (52.1%) LCC. LCC was more likely to metastasize to the liver and lung. Kaplan-Meier curves demonstrated that LCC patients had better overall and cancer-specific survival outcomes. Among Cox multivariate analyses, LCC was associated with a slightly reduced risk of overall survival (HR, 0.92; 95% CI, 0.92-0.93) and cancer-specific survival (HR, 0.92; 95% CI, 0.91-0.93), even after adjusted for other variables. However, the relationship between location and prognosis was varied by subgroups defined by age, year at diagnosis, stage, and therapies. Conclusions. We demonstrated that LCC was associated with better prognosis, especially for patients with distant metastasis. Future trails should seek to identify the underlying mechanism.